The effect of psychiatric clerkship, educational phase, contact with mental illness and gender on stigma and mental health help-seeking attitude in medical students in Jordan - Bara’ Jaser Abuistaitah; Ehab Eyad Abu Al-Feilat; Hamid Ahmad Al-Qaralleh; Amro Emad AlMomani; Hafezaldeen Jamal Hamam; Radwan Ali BaniMustafa; Abdallah Barjas Qaswal (Middle East Current Psychiatry)
Abstract Background and aims Stigma is considered a significant barrier to help-seeking and it is more prominent in medical students. Studies exploring stigma and its impact on Attitude Towards Seeking Professional Psychiatric Help (ATSPPH) among medical students in Jordanian universities are scarce. In this paper, we aim to assess the level of stigma among Jordanian medical students and its relationship with help-seeking and other secondary factors. Methods A cross-sectional study conducted through an online questionnaire on medical students in Jordan, the survey included validated psychometric tools Mental Health Clinicians Attitude 2 (MICA-2) and Attitude Towards Seeking Professional Psychiatric Help Short Form (ATSPPH-SF) in addition to sociodemographics. Stigma was analysed as a correlate of help-seeking using Spearman’s rank besides the non-parametric analysis of secondary factors. Results A total of 390 responses were analysed, 224 were females and 201 had experience with mental illness. There is an inverse relationship between stigma and ATSPPH p-value < .001. Jordanian medical students show relatively higher stigma compared to students from other nations. Females showed significantly less stigmatizing attitude p-value < .001 and more positive ATSPPH p-value < .001 compared to males. Individuals who encountered mental illness had significantly less stigma and more positive help-seeking behaviour compared to the opposite group. (p-value = .002 and p-value < .001) respectively. Completing a psychiatric clerkship had no impact on help-seeking. Conclusion Medical students in Jordan show a highly stigmatizing attitude compared with students from other nations. In parallel with the literature, females and students who experienced mental illness show less stigmatizing attitudes and more positive help-seeking behaviour.